Cognitively Impaired Older Persons' and Caregivers' Perspectives on Dementia‐Specific Advance Care Planning. Issue 4 (20th November 2020) - Fried, Terri R.; Cohen, Andrew B.; Harris, Joanna E.; Moreines, Laura
Abstract : Background/Objectives: Advance care planning (ACP) traditionally involves asking individuals about their treatment preferences during a brief period of incapacity near the end of life. Because dementia leads to prolonged incapacity, with many decisions arising before a terminal event, it has been suggested that dementia‐specific ACP is necessary. We sought to elicit the perspectives of older adults with early cognitive impairment and their caregivers on traditional and dementia‐specific ACP. Design: Qualitative study with separate focus groups for patients and caregivers. Setting: Memory disorder clinics. Participants: Twenty eight persons aged 65+ with mild cognitive impairment or early dementia and 19 caregivers. Measurements: Understanding of dementia trajectory and types of planning done; how medical decisions would be made in the future; thoughts about these decisions. Results: No participants had engaged in any written form of dementia‐specific planning. Barriers to dementia‐specific ACP emerged, including lack of knowledge about the expected trajectory of dementia and potential medical decisions, the need to stay focused in the present because of fear of loss of self, disinterest in planning because the patient will not be aware of decisions, and the expectation that involved family members would take care of issues. Some patients had trouble engaging in the discussion. Patients had highly variable views on what the quality of their future life would be and on the leeway their surrogates should have in decision making. Conclusions: Even among patients with early cognitive impairment seen in specialty clinics and their caregivers, most were unaware of the decisions they could face, and there were many barriers to planning for these decisions. These issues would likely be magnified in more representative populations, and highlight challenges to the use of dementia‐specific advance directive documents.